DEM analyses of shear behaviour of rock joints by a novel bond contact model. (August 2015) - Jiang, M J; Liu, J; Sun, C; Chen, H
Abstract: The failure of rock joints is one of the potential causes for the local and general rock instability, which may trigger devastating geohazards such as landslide. In this paper, the Distinct Element Method (DEM) featured by a novel bond contact model was utilized to simulate shear behaviour of centre/non-coplanar rock joints. The DEM results show that the complete shear behaviour of jointed rock includes four stages: elastic shearing phase, crack propagation, the failure of rock bridges and the through-going discontinuity. The peak shear strength of centre joint increases as the joint connectivity rate decreases. For intermittent noncoplanar rock joints, as the inclination of the rock joints increases, its shear capacity decreases when the inclination angle is negative while increase when positive. Comparison with the experimental results proves the capability of this DEM model in capturing the mechanical properties of the jointed rocks.